Analisis Pemangku Kepentingan dalam Upaya Pemulihan Ekosistem Daerah Tangkapan Air Danau Toba (Stakeholder Analysis on Ecosystem Restoration of Lake Toba Catchment Area) - Leti Sundawati; S Sanudin (Institut Pertanian Bogor (IPB University), 2009)
Increasing population and exploitation of Toba Lake catchment area had caused environmental degradation. Various institutions attempt to rehabilitate the area, including Ministry of Forestry through the ITTO project. The project aims to gather all stakeholders of restoration of Toba Lake catchment area ecosystem and facilitate them to exchange knowledge and information, so that they could have same understanding and build a network. This study was conducted in 3 districts, i.e. Samosir, Simalungun, and Karo. The respondents were selected using snowball sampling. The data was analyzed using stakeholder mapping. The study shows that key stakeholders of Lake Toba catchment area ecosystem restoration are government institutions which their role and functions are still limited according their main tasks which hindered synergic activities among them. There are potential conflict and collaboration among stakeholders which should be managed for the benefit of the project.